Role of salivary leukocyte protease inhibitor in periodontal disease progression - Pateel Deepak; Seema H; Kale Akla (Wolters Kluwer Medknow Publications, 2010)
Context: Proteases play a major role in the tissue destruction involved in periodontal disease. It is known that the balance between proteases and their inhibitors is a major determinant in maintaining tissue integrity. The association between the proteases and periodontitis is well established, but not many studies have been carried out to know the role played by a protease inhibitor like salivary leukocyte protease inhibitor (SLPI) in periodontitis. Aim: The aim of the present study was to correlate SLPI with periodontitis. Settings and Design: Case-control study. Materials and Methods: Seventy-five clinically confirmed cases of periodontitis and 20 controls were included in the study. A detailed case history and periodontal index (PI) were recorded. Two milliliters of unstimulated saliva samples was obtained and subjected to quantification of SLPI leaves using SLPI in enzyme-linked immunosorbent assay (ELISA) kit. Based on the periodontal index score of the individuals, the cases and controls were divided into groups A, B and C, and the obtained SLPI levels were compared among the groups. Statistical Analysis: Mann-Whitney U test and correlation coefficient test. Results: The results showed that in the initial stages of periodontitis there is a tendency of SLPI levels to be raised. The SLPI levels were found to be reduced in the terminal stages of periodontitis. Conclusion: It appears that SLPI accumulates in the local environment, at least in the initial stages of the periodontal disease, probably to inhibit the action of increased elastic activity.